2020
DOI: 10.2196/24125
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Weibo Social Media Posts From Wuhan, China During the Early Stages of the COVID-19 Pandemic: Qualitative Content Analysis

Abstract: Background The COVID-19 pandemic has reached 40 million confirmed cases worldwide. Given its rapid progression, it is important to examine its origins to better understand how people’s knowledge, attitudes, and reactions have evolved over time. One method is to use data mining of social media conversations related to information exposure and self-reported user experiences. Objective This study aims to characterize the knowledge, attitudes, and behaviors… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 23 publications
2
21
1
Order By: Relevance
“…Moreover, social media is one of the most popular media for information dissemination and distribution, with 20%-87% usage surging during the crisis [ 23 ]. Recently, Oxford’s Reuters Institute investigated the dissemination of misinformation and found that a majority (88%) of the misinformation about COVID-19 originated from social media [ 24 ]. In Italy, approximately 46,000 posts posted per day on social media in March 2020 were linked to COVID-19 misinformation [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, social media is one of the most popular media for information dissemination and distribution, with 20%-87% usage surging during the crisis [ 23 ]. Recently, Oxford’s Reuters Institute investigated the dissemination of misinformation and found that a majority (88%) of the misinformation about COVID-19 originated from social media [ 24 ]. In Italy, approximately 46,000 posts posted per day on social media in March 2020 were linked to COVID-19 misinformation [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In December 2019, the novel coronavirus originated from Wuhan, China and quickly emerged as the greatest global public health threat [1][2][3][4]. Following this, scientists mobilized to investigate different aspects of the pandemic, including its potential consequences for societies using online data [5].…”
Section: Introductionmentioning
confidence: 99%
“…We specifically choose to examine the early outbreak period in the United States as it represents a critical time frame of formation of public perception, knowledge dissemination, and initial behavior adaptation towards public health interventions, which can influence subsequent behaviors and attitudes towards the pandemic in later stages [25]. Other studies have similarly examined other social media platforms (e.g., Chinese microblogging platform Weibo) at the early stages of COVID-19 in other countries for public perception and sentiment, such as in Wuhan City, China, where the outbreak originated [26][27][28].…”
Section: Introductionmentioning
confidence: 99%